Integrating Blockchain Technology for Air Purifier Production System at FIM Learning Factory - Mohd Ridzuan, Darun; Al Adresi, Alaeldeen Saleh; Turi, Jamshid Ali; Mohd Ghazali, Maarof (Science & Engineering Research Support society, 2020)
This paper focuses on the use of blockchain technology in the production process of the air purifier through a learning factory collaboration concept, which emphasizes more on the academic and industrial liaisons for innovation and development among partners. The partners agreed to use learning factory concepts through collaboration between academia and industry for the production planning and design, plant automation, execution, maintenance, services, and quality enhancement. Moreover, it has also described the rationale for using blockchain technology for the production of air purifiers and the strategies of the supply chain activities incumbent for the manufacturing processes of the air purifier. Furthermore, for supply chain activities were integrated with the blockchain technology in order to identify the blocks and data during the process flow. This paper also explains a synchronization process flow and integration for the smoother operation of the manufacturing processes of the Air purifier using blockchain technology. Potential industrial challenges of the Air purifier construction and development have been highlighted. The review results indicate the significance of using blockchain technology to meet energy needs around the globe; it will give new directions and philosophies to the industrial processes of manufacturing high-quality cost-effective Air purifiers efficiently and effectively, fulfilling the needs and expectations of the customers.